2019
DOI: 10.1002/lt.25361
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence of Nonalcoholic Steatohepatitis as an Indication for Liver Transplantation in Australia and New Zealand

Abstract: The worldwide increase in obesity and diabetes has led to predictions that nonalcoholic steatohepatitis (NASH) will become the leading indication for orthotopic liver transplantation (OLT). Data supporting this prediction from outside the United States are limited. Thus, we aimed to determine trends in the frequency of NASH among adults listed and undergoing OLT in Australia and New Zealand (ANZ) from 1994 to 2017. Data from the ANZ Liver Transplant Registry were analyzed with patients listed for fulminant liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 32 publications
2
30
0
8
Order By: Relevance
“…We would then be able to analyze the impact of the degree of liver fibrosis and disease severity on outcomes. In 2017, patients with NAFLD accounted for an alarming 10% of patients undergoing liver transplantation in the United States [30]. Our study reinforces the need for further investigation of NAFLD related all-cause mortality in terms of gender differences.…”
Section: Discussionsupporting
confidence: 68%
“…We would then be able to analyze the impact of the degree of liver fibrosis and disease severity on outcomes. In 2017, patients with NAFLD accounted for an alarming 10% of patients undergoing liver transplantation in the United States [30]. Our study reinforces the need for further investigation of NAFLD related all-cause mortality in terms of gender differences.…”
Section: Discussionsupporting
confidence: 68%
“…Based on expert input and analysis of diagnostic categories for transplant recipients, it was estimated that approximately 15% of current liver transplants are attributable to NAFLD/NASH. Analysis of liver transplant data from Australia and New Zealand has shown that NASH as an indicator grew from 2.0% in 2003 to 10.9% in 2017, making it the third leading indicator for liver transplants . Given the uncertainties around transplant demand and availability, it was assumed that the annual number of transplants would remain constant through 2030.…”
Section: Methodsmentioning
confidence: 99%
“…Data from the European Transplant Registry also show an increase in transplantation for NAFLD-related HCC from 0.2% in 2007 to 1.2% in 2017 [40] . In Australia and New Zealand, NAFLD is the third leading cause of HCC in those who underwent transplantation, and an Australian cohort of 272 HCC patients found NAFLD to be the underlying aetiology with 14% of cases [41,42] . A summary of these cohorts is outlined in Table 1.…”
Section: Prevalence Of Nafld-related Hccmentioning
confidence: 99%